Pengembangan Media Pembelajaran Interaktif Berbasis Android untuk Meningkatkan Pemahaman Konsep Matematika Siswa SMP: The Development of an Android-Based Interactive Learning Medium to Enhance the Mathematical Concept Understanding of Junior High School Students - Nurholipah, Nurholipah (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aimed to develop an Android-based interactive learning medium to enhance the mathematical concept understanding of junior high school students. The research employed a Research and Development (R&D) method with the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of three expert validators (content, media, and language) and 30 eighth-grade junior high school students for a trial to test its effectiveness. The research instruments included expert validation sheets, student and teacher response questionnaires, and a test of mathematical concept understanding. The expert validation results indicated that the application was feasible for use, with percentages of 85.4% (content expert), 87.2% (media expert), and 83.6% (language expert). The effectiveness test, using a pretest-posttest design, demonstrated a significant increase in mathematical concept understanding with an N-Gain score of 0.73 (high category). Student responses showed that 89.3% found the application easy to use, 91.7% found it engaging, and 88.6% found it beneficial for learning. The Android-based interactive learning medium was proven effective in enhancing the mathematical concept understanding of junior high school students and can be recommended as a modern learning alternative.